Changes to virus taxonomy and the ICTV Statutes ratified by the International Committee on Taxonomy of Viruses (2023) - Zerbini, Francisco Murilo; Siddell, Stuart G.; Lefkowitz, Elliot J.; Mushegian, Arcady R.; Adriaenssens, Evelien M.; Alfenas‑Zerbini, Poliane; Dempsey, Donald M.; Dutilh, Bas E.; García, María Laura; Hendrickson, R. Curtis; Junglen, Sandra; Krupovic, Mart; et al. (Archives of virology, 2023)
This article reports changes to virus taxonomy and taxon nomenclature that were approved and ratified by the International Committee on Taxonomy of Viruses (ICTV) in April 2023. The entire ICTV membership was invited to vote on 174 taxonomic proposals that had been approved by the ICTV Executive Committee in July 2022, as well as a proposed revision of the ICTV Statutes. All proposals and the revised ICTV Statutes were approved by a majority of the voting membership. Of note, the ICTV continued the process of renaming existing species in accordance with the recently mandated binomial format and included gene transfer agents (GTAs) in the classification framework by classifying them as viriforms. In total, one class, seven orders, 31 families, 214 genera, and 858 species were created.